Tied aid, trade-facilitating aid or trade-diverting aid? - Lars M. Johansson; Jan Pettersson (Uppsala University, Department of Economics, 2009)
Donor aid is often regarded as being informally tied (aid increases donorrecipient exports) and this effect is, in general, interpreted as being harmful to aid recipients. However, in this paper, using a gravity model, we show that aid is also positively associated with recipient-donor exports. That is, aid increases bilateral trade ows in both directions. Our interpretation is that an intensi ed aid relation reduces the e ective cost of geographic distance. We find a particularly strong relation between aid in the form of technical assistance and exports in both directions. When we disaggregate aid to specifically study the effects from trade-related assistance (Aid for Trade) the effect is small and fully accounted for by aid to investments in trade-related infrastructure. Our sample includes all 184 countries for which data is available during the period 1990 to 2005.
urn:nbn:se:uu:diva-101264
Keywords: F35; O19; O24; 330; Foreign Aid; International Trade; Exports; Gravity; Aid for Trade; Entwicklungshilfe; Internationale Handelspolitik; Internationale Wirtschaftsbeziehungen; Gravitationsmodell; Welt